Respuesta :
ƒ(x) = 1/2x + 4
inverse
x = 1/2 y + 4
2x = y + 8
y = 2x - 8
so inverse f-1(x) = 2x - 8
ƒ -1(4) = 2(4) - 8 = 0
answer
ƒ -1(x) = 2x - 8
ƒ -1(4) = 0
inverse
x = 1/2 y + 4
2x = y + 8
y = 2x - 8
so inverse f-1(x) = 2x - 8
ƒ -1(4) = 2(4) - 8 = 0
answer
ƒ -1(x) = 2x - 8
ƒ -1(4) = 0
Answer:
[tex]f^{-1}(x) = 2x - 8\\ f^{-1}(4) = 0[/tex]
Step-by-step explanation:
To find an inverse function, we need to think the function as an equality x = 1/2y + 4 that we have to resolve for the y.
First, let's subtract 4 from both sides.
x - 4 = 1/2y + 4 - 4
x - 4 = 1/2y
Now we multiply by 2 on both sides.
(x-4)*2 = 1/2y*2
2*x-8 = y
Therefore, the inverse function is
[tex]f^{-1}(x)=2x-8[/tex]
To find out [tex]f^{-1}(4)[/tex], we need to replace the x of the function with a 4:
[tex]f^{-1}(4)[/tex] = 2*4 - 8 = 8 - 8 = 0
[tex]f^{-1}(4)[/tex]= 0